(untitled) (Research, Society and Development, 2021)
Bisphosphonates act in the bone remodeling process, preventing pathological resorption caused by certain diseases such as osteoporosis, osteogenesis imperfecta, Paget’s disease and neoplasms with bone metastases. The bisphosphonate incorporates into the bone matrix due to its high affinity with bone, characterizing its cumulative effect and providing the risk of developing osteonecrosis of the jaws induced by bisphosphonates, which is a complication arising from the use of these drugs where there is a pathological necrotic bone exposure of jawbones, which may arise spontaneously or be induced by dental interventions. The aim of this study is to understand osteonecrosis and its etiology to identify local or systemic risk factors, prevention methods, and to show means of diagnosis through clinical signs and symptoms and complementary exams, in addition to staging it in case of occurrence and the respective existing treatments. For the construction of the literature review some steps were determinant as the elaboration of guiding questions and hypotheses, literature search for data collection following inclusion and exclusion criteria through detailed analysis and interpretation of results. With the aging of the population, the number of people using antiresorptive medications has increased significantly, and with this, the risk of developing complications such as this one has also increased. We conclude that the role of the dental surgeon in a multidisciplinary team is extremely important for the treatment of these individuals who use this type of drug to prevent and reduce the occurrence of osteonecrosis, guaranteeing assistance, health, and well-being to the patient.